Facile preparation of an effective intumescent flame-retardant coating for cotton fabric. Issue 3 (24th May 2020) - Cheng, Xian-Wei; Wu, Yan-Xiang; Hu, Bi-Qing; Guan, Jin-Ping
Abstract : In the present study, phytic acid was used as an environmentally sustainable phosphorus-containing flame retardant (FR) to improve the flammability of cotton fabrics. The facile preparation approach is adequate for offering an intumescent FR system for cotton, as phytic acid and triethanolamine could serve as the acid source and blowing agent, respectively, and a cellulose substrate may function as the carbon source. The flame retardancy, thermal stability, heat and smoke generation and mechanical performance of cotton fabrics were evaluated. The cotton fabrics coated with 70 g/l phytic acid at pH 5 had a weight gain of 15.1% and self-extinguished by way of an intumescent charring mechanism in the vertical burning test, and the textile structures of the burned portion were well preserved. The intumescent FR coating also greatly reduced the heat and smoke generation ability of cotton and enhanced its thermal stability at high temperature, but it suffered from poor washing resistance. The present intumescent FR system based on phytic acid is an eco-friendly and sustainable production approach compared with synthetically engineered chemicals.